Perceived precarious life: a SEM model for re-dimensioning of precarious work and its impact on mental health - Llosa, José Antonio; Agulló-Tomás, Esteban; Menéndez-Espina, Sara; Rivero-Díaz, María Luz (Frontiers in Public Health, 2024)
Introduction: Precarious work is one of the most studied concepts related to work, and its effects have been analysed in relation to variables such as mental health and well-being. However, there is a tendency to atomise the analysis of precarious work, without understanding that people's working life is intertwined with other areas of their life. Objective: Faced with this situation, this paper presents the concept of perceived precarious life, which is aligned with contemporary models of social inclusion and exclusion. Thus, perceived precarious life comprises variables of labour precariousness, social support and hopelessness in the family economic situation. Methods: To test this idea, a structural equation model (SEM) is presented, which tests the structure of the construct of perceived precarious life by relating it to mental health and coping strategies. Results: After testing the fit of the model in both men and women, a SEM path analysis is designed between the variables, observing that perceived precarious life has an effect on mental health (β = .635, p<.01). This relationship is mediated by unproductive coping strategies (β = .142, p<.01). Conclusion: This model exposes a broad and integrated conceptualisation of precariousness, combining aspects of work, relationships and hopelessness, which allows for an understanding of the integral experience of precariousness.